Quantifying the magnitude of stress among new graduate nurses working in intensive care units - Aida Sanad Alqarni; Lorraine Estadilla; Ferdinand Gonzales; Eddieson Pasay-an; Abdulellah Alotaibi; Osama Alkouri; Sahar Hamdy El-Sayed; Enas Mohammed Bassuni; Kawther Eltayeb Ahmed; Abdulellah Bin Modhi Al-Solais; Heba A. Al-Metyazidy (Scientific Reports)
Abstract Nurses working in Intensive Care Units are prone to burnout and low job satisfaction which can be caused by stress. This cross-sectional study aimed to quantify the magnitude of stress among new graduate nurses working in ICUs. A survey was conducted between May and July 2023 at the 11 adult and pediatric ICUs in King Saud Medical City, Riyadh (KSMC-R). Using convenience sampling, 189 participants were recruited. A significant difference was found in the mean total Perceived Stress Scale (PSS)-10 and Expanded Nursing Stress Scale (ENSS)- 10 scores between the males and females. In the subscales, significant differences were seen between the workload and gender, age group, and type of ICU and in the mean inadequate emotional preparation scores and age group and marital status, type of ICU (adult/pediatric), and the different types of ICU. The survey showed that the major factors that caused stress among the new graduate nurses were discrimination, problems with supervisors, workload, problems with peer support, uncertainty concerning treatment, and dealing with patients and their families.